From Sangbai to Sangbaian Pangigalan: Tracing the Evolution of the Contemporary - Santamaria, MCM (Philippine Social Sciences Review; PSSR Vol. 66 No. 2, 2014, Ed. Ma. Luisa T. Camagay, 2015)
Sangbaian pangigalan is a contemporary linked song-anddance expression found among the Sama-Bajau (Sama or Sinamaspeaking) peoples of the southern Philippines and Sabah, Malaysia. It is usually performed during lami-lamian or merry-making evenings that precede pagkawin or wedding celebrations and other festive occasions. In this genre, a singer performs a song accompanied by an electronic organ or synthesizer while a dancer performs a modern form of igal dance. Igal is the Sama-Bajau traditional dance genre which is characterized by postures and transitional gestures that are reminiscent, among others, of those found in Balinese, Thai, and Khmer dance traditions. In the contemporary expression of sangbaian pangigalan, the singer and the dancer interact throughout the whole performance. How this song-dance expression is related to other performance traditions of the Sulu Sea area such as the pangalay, the dalling-dalling, and the pagsangbay is not clear. This article proposes to examine the relationship of the sangbaian pangigalan and these aforementioned forms through a critical review of dance studies literature, an examination of examples of the genre observed in the field, and an analysis of samples captured in commercial video recordings. Part 1 describes the initial encounters with the sangbaian pangigalan. Part 2 reviews literature that relates the sangbaian pangigalan to pangalay, igal, pagsangbay, and dalling-dalling. By way of conclusion, Part 3 presents a (re)construction of the lineage of the sangbaian pangigalan that incorporates data from past research and new forms observed in the field.
Keywords: Sangbaian pangigalan, Sama-Bajau performance, ethno-choreology, dance history